PENGARUH PENDIDIKAN KESEHATAN MINUM OBAT TERHADAP KEPATUHAN MINUM OBAT PASIEN TUBERKULOSIS DIWILAYAH PUSKESMAS SALIBABU - Vani Y Tampilang; Thirsa O Mongi; Marice Tatulus (JURNAL ILMIAH KESEHATAN MANADO, 2025)
This study is a quantitative study that uses a Quasi-experimental research design type. The research design used was One-Group Pre-Post test Design, the time was in December 2024 and the research location was at the Tateli Health Center, Mandolang District, Minahasa Regency. The sampling technique used a total population of 23. The statistical test used was the "Chi-Square" statistical test with a confidence level of 95%. The results of the study obtained a P value = 0.002 while the α value = 0.05 so that the P value = 0.002 <α = 0.05. Conclusion From the results of the study. The results of the study showed that the compliance of taking medicine for Pulmonary TB patients before being given Health Education was more compliant. The results of the study showed that the compliance of taking medicine for Pulmonary TB patients before being given Health Education was more compliant. There is an Effect of Health Education on Compliance in Taking Medicines for Pulmonary Tuberculosis Patients in the Salibabu Health Center Area.